Circulating levels of five proglucagon-derived peptides in response to intravenous or oral glucose or lipids and to a mixed-meal in subjects with normal weight, overweight, and obesity. Issue 9 (September 2022) - Perakakis, Nikolaos; Kokkinos, Alexander; Angelidi, Angeliki M.; Tsilingiris, Dimitrios; Gavrieli, Anna; Yannakoulia, Maria; Tentolouris, Nicholas; Mantzoros, Christos S.
Summary: Aims: Proglucagon-derived peptides (PGDPs) secreted by the gut and pancreas play a major role in metabolism. We measured concentrations of five PGDPs in response to per os (PO) or intravenous (IV) glucose or lipid intake and a mixed meal test (MMT) consumed by subjects with normal weight, overweight or obesity. Materials and methods: GLP-1, oxyntomodulin and glicentin (gut-secreted PGDPs) and glucagon and MPGF (pancreas-secreted PGDPs) were assessed in: (a) 32 subjects receiving PO or IV glucose, lipids or water over 6 h, (b) 33 subjects with normal weight, overweight or obesity who consumed a MMT. Results: (a) GLP-1, oxyntomodulin, glicentin and glucagon levels increase more profoundly and persistently after lipids PO (2.5 g/kg) than glucose PO (2.5 g/kg) or IV lipids (Intralipid/Liposyn II 20% at 0.35 ml/kg/h and Intralipid/Liposyn II 20% at 0.83 ml/kg/h for 6 h) or IV glucose (10% glucose at 3.6 ml/kg/h for 6 h). Oxyntomodulin and glicentin increased more than GLP-1 in response to lipids PO. MPGF levels decrease in response to glucose PO or IV indicating a shift towards preferential production of gut-secreted peptides. (b) Fasting and postprandial areas under the curve (AUCs) after MMT of GLP-1, MPGF and glucagon levels correlated positively with BMI. The fasting levels of glucagon and MPGF were elevated in obesity and remained elevated after the MMT. Conclusion: Circulating levels of PGDPs are differentially regulated by body weight, the type of macronutrients administered and the respective route of administration. Mechanistic studies are needed to define the exact mechanisms underlying this regulation. Clinical Trial Registration: Study 1 has the NCT01520454 and the NCT04888325 number in ClinicalTrials.gov . Study 2 has the number NCT01495754 in ClinicalTrials.gov .